IMPACT OF THE COVID-19 OUTBREAK ON SURGICAL MANAGEMENT OF MUSCULOSKELETAL ONCOLOGY PATIENTS: A MULTI-CENTER PROSPECTIVE COHORT STUDY - Khan, Zeeshan; Badar Uddin Sahito; Muhammad Arif Khan (Journal of Postgraduate Medical Institute, 2021)
Objective: To evaluate the impact of the Covid-19 outbreak on surgical management of musculoskeletal oncology patients. Methodology: A total of 76 patients were identified and included in this observational study for which data was collected from the databases of Hayatabad Medical Complex, Peshawar & Dr. Ruth KM Pfau Civil Hospital, Karachi, Pakistan from March till August 2020. Patients having malignant bone and soft tissue tumours and locally aggressive benign tumours were included in this study. All the patients underwent PCR investigation for SARS-CoV-19 virus pre-operatively and surgeries were performed in PCR negative and asymptomatic PCR positive patients only, with protective equipment. Results: In sample, 8 patients tested positive for Covid-19, out of which 2 were asymptomatic and hence surgery was performed. The remaining 6 were sent for home isolation, of which 2 did not return for surgery. Five patients had ablative surgery due to disruption in medical services whereas the initial plan was for limb salvage surgery. Eight patients developed complications while 2 patients passed away in the post-operative period. None of the patients had any Covid 19 related morbidity or mortality. Conclusion: The study concluded that only a minute number of patients were suffered due to Covid-19 results. Disruption in services due to Covid-19 outbreak has impacted the efficient delivery of health care in various specialties including serious pathologies like musculoskeletal tumours.